Analisa Hukum Terhadap Kompetensi Penyidik Polisi Militer TNI AU Untuk Menjawab Tantangan Kejahatan Siber (Cyber Crime). - Tamrin, Tamrin; Widarto, Bambang; Sudarto, Sudarto (FOCUS, 2025)
The Air Force Military Police is a unit carrying out the duties and functions of the Indonesian Air Force, which includes carrying out law enforcement and investigating cases within the Air Force, one of which is cyber crime cases involving TNI Air Force personnel. This is very interesting to study further regarding the current legal arrangements and competence of Indonesian Air Force Military Police investigators to answer the challenges of cyber crime as well as obstacles in the strategy to increase the competency of Indonesian Air Force Military Police investigators and efforts to improve legal regulations to answer the challenges of cyber crime. The research method used is normative juridical law with an analysis of statutory and conceptual approaches. Data obtained from primary, secondary and tertiary legal material sources were collected and then analyzed using qualitative data analysis techniques. From the research results, it was found that the regulation of military criminal law regarding cyber crimes by members of the Indonesian Air Force is Law Number 31 of 1997 concerning Military Justice, the Criminal Code (KUHP), Law (UU) Number 1 of 2024 concerning the Second Amendment to Law Number 11 of 2008 concerning Information and Electronic Transactions. Obstacles in the strategy to increase the competency of Indonesian Air Force Military Police investigators and efforts to improve legal regulations to address the challenges of cyber crime: budget limitations, availability of human resources, lack of facilities and technology, changes in regulations and technology, coordination and cooperation, complex case challenges, ongoing evaluation and development.